Electron & Biomass Dynamics of Cyanothece Under Interacting Nitrogen & Carbon Limitations - Rabouille, Sophie; Campbell, Douglas A.; Masuda, Takako; Zavřel, Tomáš; Bernát, Gábor; Polerecky, Lubos; Halsey, Kimberly; Eichner, Meri; Kotabová, Eva; Stephan, Susanne; Lukeš, Martin; Claquin, Pascal; et al. (Frontiers in Microbiology, 2021)
Marine diazotrophs are a diverse group with key roles in biogeochemical fluxes linked to primary productivity. The unicellular, diazotrophic cyanobacterium Cyanothece is widely found in coastal, subtropical oceans. We analyze the consequences of diazotrophy on growth efficiency, compared to NO3--supported growth in Cyanothece, to understand how cells cope with N2-fixation when they also have to face carbon limitation, which may transiently affect populations in coastal environments or during blooms of phytoplankton communities. When grown in obligate diazotrophy, cells face the double burden of a more ATP-demanding N-acquisition mode and additional metabolic losses imposed by the transient storage of reducing potential as carbohydrate, compared to a hypothetical N2 assimilation directly driven by photosynthetic electron transport. Further, this energetic burden imposed by N2-fixation could not be alleviated, despite the high irradiance level within the cultures, because photosynthesis was limited by the availability of dissolved inorganic carbon (DIC), and possibly by a constrained capacity for carbon storage. DIC limitation exacerbates the costs on growth imposed by nitrogen fixation. Therefore, the competitive efficiency of diazotrophs could be hindered in areas with insufficient renewal of dissolved gases and/or with intense